Fabrication and Photoluminescence Properties of Monodispersed SiO2@SrAl2Si2O2:Eu2+ Core-Shell Submicron Spheres - Zhang, J.M.; Zhao, D.L.; Zhang, D.D.; Shen, Z.M. (Asian Journal of Chemistry, 2014)
Nanocrystalline SrAl2Si2O8:Eu2+ phosphor layers were coated on the surface of preformed submicron silica spheres by sol-gel method. The resulted monodispersed SiO2@SrAl2Si2O8:Eu2+ core-shell submicron spherical phosphors were characterized by X-ray diffraction, scanning electron microscopy, transmission electron microscopy and photoluminescence spectra. The XRD results demonstrated that the SrAl2Si2O8:Eu2+ layers began to crystallize on the SiO2 spheres at 900 °C and the crystallinity increased with raising the annealing temperature. The obtained monodispersed core-shell spherical phosphors have perfect spherical shape with narrow size distribution (average size 500 nm). The Eu2+ shows a strong photoluminescence (dominated by 4f65d1 ® 4f7 red emission at 390 nm) due to an efficient energy transfer from vanadate groups to Eu2+. The photoluminescence intensity of Eu2+ increases with raising the annealing temperature.